Conceptions of Mental Illness: Attitudes of Mental Health Professionals and the General Public - Stuber, Jennifer P. (2014)
OBJECTIVES: The authors compared attitudes of the U.S. general public and of mental health professionals about the competence and perceived dangerousness of people with mental health problems and the desire for social distance from them. Factors related to negative attitudes and the desire for social distance also were examined. METHODS: Vignettes describing individuals meeting DSM-IV criteria for major depression and schizophrenia were included in the 2006 General Social Survey (GSS) and a 2009 study of mental health professionals, and responses were descriptively compared (GSS, N=397 responses to depression vignette, N=373 responses to schizophrenia vignette; 731 mental health professionals responded to both vignettes). Regression analyses examined whether demographic and provider characteristics were associated with perceptions of less competence and perceived dangerousness of the vignette character and with respondents’ desire for social distance. RESULTS: Compared with the American public, mental health professionals had significantly more positive attitudes toward people with mental health problems. However, some providers’ conceptions about the dangerousness of people with schizophrenia and provider desire for social distance from clients in work and personal situations were concerning. Younger age, self-identifying as non-Hispanic white, being female, having at least a four-year college degree, being familiar with mental illness, and certain job titles and more years of experience in the mental health field were predictive of more positive conceptions. CONCLUSIONS: Although mental health professionals held more positive attitudes than the general public about people with mental health problems, strong stereotypes persisted in both groups, especially concerning schizophrenia. This study identified several demographic and provider characteristics that can inform intervention strategies in both groups.